Fergus Crane - Stewart, Paul 1955-; Riddell, Chris 1962- (David Fickling Books, 2006)
Nine-year-old Fergus Crane's life is filled with classes on the school ship Betty Jeanne, interesting neighbors, and helping with his mother's work until a mysterious box flies into his window and leads him toward adventure
Keywords: Adventure and adventurers / Fiction; Inventions / Fiction; Pirates / Fiction; Ships / Fiction; Adventure stories; Inventions / Juvenile fiction; Pirates / Juvenile fiction; Ships / Juvenile fiction; Seeräuber; Abenteuer; Schulschiff; Kinderbuch